Analysis of transcriptome and differential expression of different types of calli of Eucalyptus urophylla × Eucalyptus grandis - Yamei Liu; Chaohong Wang; Lejun Ouyang; Limei Li; Min Su (PLoS ONE, 2025)
Eucalyptus urophylla X Eucalyptus grandis is an important afforestation hybrid clone that supports wood safety in China. To explore the mechanism of callus formation and differentiation of different types of E. urophylla × E. grandis, we cultivated four different types of E. urophylla × E. grandis calli, measured their enzyme activities and endogenous hormones, and sequenced them at the transcriptome level. Transcriptome analysis revealed that there were significant differences in the clustering of differentially expressed genes. Compared with the green calli, 2203, 2485, and 2078 differentially expressed genes were identified in the red, white, and yellow calli, respectively. Differentially expressed genes were involved in metabolic processes, biological regulation, signal transduction, stimulus response, catalytic activity, and binding, such as GRFs gene. Combined with the changes in physiological indices and transcription levels, we revealed the regulatory characteristics of substance storage and antioxidant capacity in the process of callus differentiation of E. urophylla × E. grandis, which contributes to the understanding of the mechanism of plant cell growth and differentiation.